Optical Fiber Biomedical Sensor Based on Surface Plasmon Resonance - Rahim, Namaa Salem; Ahmed, Sudad S.; Sultan, Murtadha Faaiz (Iraqi Journal of Science, 2020)
Optical fiber biomedical sensor based on surface plasmon resonance for measuring and sensing the concentration and the refractive index of sugar in blood serum is designed and implemented during this work. Performance properties such as signal to noise ratio (SNR), sensitivity, resolution and the figure of merit were evaluated for the fabricated sensor. It was found that the sensitivity of the optical fiber-based SPR sensor with 40 nm thick and 10 mm long Au metal film of the exposed sensing region is 7.5Âµm/RIU, SNR is 0.697, figure of merit is 87.2 and resolution is 0.00026. The sort of optical fiber utilized in this work is plastic optical fiber with a core diameter of 980 Âµm, a cladding of 20Î¼m, and a numerical aperture of 0.51.